2007
DOI: 10.1128/aac.00646-07
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Reverse Transcriptase and RNase H Domain Mutations in Human Immunodeficiency Virus Type 1 Clinical Isolates Are Associated with Divergent Phenotypic Resistance to Zidovudine

Abstract: Mutations in the RNase H domain of human immunodeficiency virus type 1 RT have been reported to cause resistance to zidovudine (ZDV) in vitro. However, very limited data on the in vivo relevance of these mutations in patients exist to date. This study was designed to determine the relationship between mutations in the RNase H domain and viral susceptibility to nucleoside analogues. Viruses harboring complex thymidine analogue mutation (TAM) and nucleoside analogue mutation (NAM) profiles were evaluated for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…It is noteworthy that in our survey of subtype B viruses, substitutions at positions 369 and 348 were more prevalent in viruses from treatment-experienced patients than in viruses from treatment-naïve individuals. This observation is in agreement with recent publications reporting a higher prevalence of N348I in RTI-experienced patients, the association of N348I with NRTI (M184V/I [TAMs]) and NNRTI (K103N, Y181C) resistance mutations, and the selection of N348I during NVP and ZDV treatment (20,36 (5,19). In our survey, mutations at 369 and 348 were not observed in non-subtype B viruses.…”
Section: Discussionsupporting
confidence: 82%
“…It is noteworthy that in our survey of subtype B viruses, substitutions at positions 369 and 348 were more prevalent in viruses from treatment-experienced patients than in viruses from treatment-naïve individuals. This observation is in agreement with recent publications reporting a higher prevalence of N348I in RTI-experienced patients, the association of N348I with NRTI (M184V/I [TAMs]) and NNRTI (K103N, Y181C) resistance mutations, and the selection of N348I during NVP and ZDV treatment (20,36 (5,19). In our survey, mutations at 369 and 348 were not observed in non-subtype B viruses.…”
Section: Discussionsupporting
confidence: 82%
“…A limitation of our study relates to the use of laboratory strains. However, the mutations that we identified have been reported in clinical isolates (38,45,54). Another limitation of our study relates to the lack of information on the mutations in the RNase H domain of NNRTI-treated patients, since these mutations have been reported mostly in NRTI-treated patients.…”
Section: Discussionmentioning
confidence: 42%
“…A comparison of RNase H sequences in naive versus NRTI-experienced patients in a French cohort showed that mutations L469T/I/M/H, T470P/S/E/K, A554T/L/K, and K558R/ G/E were more prevalent among treatment-experienced patients (44). However, Ntemgwa et al analyzed RNase H mutations in NRTI-experienced patients from a Canadian and an Italian cohort and found positions D460, P468, H483, K512, and S519 to be extensively polymorphic in both naive and experienced patients (38). Recently, an analysis of patient sequences from databases showed that several mutations in the connection subdomain were significantly higher for sequences that contained one or more RTI resistance mutations compared to sequences without RTI resistance mutations (16).…”
Section: Discussionmentioning
confidence: 99%
“…Certain mutations in the connection subdomain (codons 322 to 440) of the polymerase domain or in the RNase H domain (codons 441 to 560)of HIV-1 RT have been recently shown to be associated with resistance to AZT (Brehm et al, 2007; Hachiya et al, 2008; Kemp et al, 1998; Nikolenko et al, 2007; Ntemgwa et al, 2007; Yap et al, 2007). In some cases it appears that mutations that affect AZT resistance have different phenotypes, depending on the presence or absence of other resistance mutations.…”
Section: Introductionmentioning
confidence: 99%